2015
DOI: 10.1038/srep08184
|View full text |Cite
|
Sign up to set email alerts
|

A concurrent excitation and inhibition of dopaminergic subpopulations in response to nicotine

Abstract: Midbrain dopamine (DA) neurons are key players in motivation and reward processing. Increased DA release is thought to be central in the initiation of drug addiction. Whereas dopamine neurons are generally considered to be activated by drugs such as nicotine, we report here that nicotine not only induces excitation of ventral tegmental area (VTA) DA cells but also induces inhibition of a subset of VTA DA neurons that are anatomically segregated in the medial part of the VTA. These opposite responses do not cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
31
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 39 publications
12
31
1
Order By: Relevance
“…S1a) (∆Frequency: One-way ANOVA, F (4, 72)  = 10.9, p < 0.001; ∆%SWB: Kruskal-Wallis, X 2  = 10.5, df = 4, p < 0.05). Similarly to what we observed with nicotine24, a fraction of VTA DA cells were inhibited by alcohol, but the current study focuses on cells that were excited by alcohol.…”
Section: Resultsmentioning
confidence: 70%
“…S1a) (∆Frequency: One-way ANOVA, F (4, 72)  = 10.9, p < 0.001; ∆%SWB: Kruskal-Wallis, X 2  = 10.5, df = 4, p < 0.05). Similarly to what we observed with nicotine24, a fraction of VTA DA cells were inhibited by alcohol, but the current study focuses on cells that were excited by alcohol.…”
Section: Resultsmentioning
confidence: 70%
“…The functional diversity of VTA neurons has been constantly updated (Unlgess, 2004; Stamatakis et al, 2013; Root et al, 2014b; Mejias-Aponte et al, 2015; Eddine et al, 2015; Kotecki et al, 2015; Beier et al, 2015). As detailed above, the multiplexed neurotransmission of the VTA-VGluT2 neurons is an emerging factor involved in the complexity of VTA function.…”
Section: Functional Diversity By Vta Neuronsmentioning
confidence: 99%
“…Indeed, many studies have reported heterogeneous responses of specific VTA neurons (Brischoux et al, 2009; Borgkvist et al, 2011; Margolis et al, 2014; Eddine et al, 2015; Mrejeru et al 2015; Mejias-Aponte et al, 2015), and it would seem likely that this diversity is due (at least in part) to cells that are capable of multiplexed neurotransmission. With this in mind, it is clear that that the discovery of compound cell types has wide-reaching implications for our understanding of VTA circuit functions.…”
Section: Multiplexed Transmission: Future Directions and Consideratiomentioning
confidence: 99%
“…). Further investigations define a D 2 ‐receptor dependent inhibition, opening the question on the role of these neurons in nicotine reinforcement (Eddine et al., ).…”
Section: Reinforcing Properties Of Nicotine and Subsequent Neural Altmentioning
confidence: 99%